Rapid and Predictable Evolution of Admixed Populations Between Two Drosophila Species Pairs. Issue 1 (1st January 2020) - Matute, Daniel R; Comeault, Aaron A; Earley, Eric; Serrato-Capuchina, Antonio; Peede, David; Monroy-Eklund, Anaïs; Huang, Wen; Jones, Corbin D; Mackay, Trudy F C; Coyne, Jerry A
Abstract: In this article, Matute et al. report an experiment in which they generated eight interspecific admixed populations using two species pairs of Drosophila . They found that in both species pairs, and across all experimental replicates... The consequences of hybridization are varied, ranging from the origin of new lineages, introgression of some genes between species, to the extinction of one of the hybridizing species. We generated replicate admixed populations between two pairs of sister species of Drosophila : D. simulans and D. mauritiana ; and D. yakuba and D. santomea . Each pair consisted of a continental species and an island endemic. The admixed populations were maintained by random mating in discrete generations for over 20 generations. We assessed morphological, behavioral, and fitness-related traits from each replicate population periodically, and sequenced genomic DNA from the populations at generation 20. For both pairs of species, species-specific traits and their genomes regressed to those of the continental species. A few alleles from the island species persisted, but they tended to be proportionally rare among all sites in the genome and were rarely fixed within the populations. This paucity of alleles from the island species was particularly pronounced on the X -chromosome. These results indicate that nearly all foreign genes were quickly eliminated after hybridization and that selection against the minor species genome might be similar across experimental replicates.